Promoting use of waste materials for sustainable geopolymer concrete: a scientometric review - Abhishek, Chanda; Thakkar, Sonal (Vietnam Journal of Science and Technology, 2025)
The building industry considerably contributes to the use of energy, depletion of resources and emission of carbon dioxide, all of which harm the environment. Currently, this industry is moving away from cement and natural materials in favour of substitute materials lowering environmental impacts and fostering sustainability. Fly ash, metakaolin, silica fume, slag, and rice husk ash are some of the wastes that are high in aluminosilicate contents and are examples of wastes produced by industries and agriculture that can be used to make geopolymer concrete, which is a substitute in Ordinary Portland cement concrete due to its exemplary strength, stabilization at elevated temperatures, denser microstructure, elevated bond strength and opposing chemical nature. This review investigates using various industrial wastes to be used as source materials in geopolymer concrete in the scientometric review using bibliometric from Scopus. Examination of the bibliometric data that is currently available and identifying relevant publication areas, year of publication, keywords, co-authorship, countries and papers with the most citations etc. have been used to assess the current state of the art.